2014
DOI: 10.1007/s00264-013-2275-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet-rich plasma on osteochondral defects treated with mosaicplasty

Abstract: Purpose This study investigated the efficacy of platelet-rich plasma (PRP) on articular surfaces on which the mosaicplasty technique was performed. Our hypothesis was that PRP can accelerate the osseointegration process and enhance the quality of articular integrity after the mosaicplasty procedure. Methods Standard defects were created in the femoral groove of both patellofemoral joints of 12 New Zealand rabbits. PRP solution was placed inside the defect before fixation of the osteochondral autografts and inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
1
29
0
1
Order By: Relevance
“…Also, age is another important factor that may have a direct influence on the haematological character of PRP. In an animal study done by Urgas et al [16] about the efficacy of PRP on integration of osteochondral defects with mosaicoplasty, he found that PRP produced a better healing response with superior histological scores than the control group [16]. The incidence of AVN in our study was (6.7 %) in group A and (3.3 %) in group B with and overall incidence of 5 %.…”
Section: Discussionsupporting
confidence: 42%
“…Also, age is another important factor that may have a direct influence on the haematological character of PRP. In an animal study done by Urgas et al [16] about the efficacy of PRP on integration of osteochondral defects with mosaicoplasty, he found that PRP produced a better healing response with superior histological scores than the control group [16]. The incidence of AVN in our study was (6.7 %) in group A and (3.3 %) in group B with and overall incidence of 5 %.…”
Section: Discussionsupporting
confidence: 42%
“…В другой экспериментальной работе на 12 кроликах полнослойный дефект хряща коленного сустава замещали методом мозаичной аутохондропластики. Авторы сообщают о лучших результатах мозаичной аутохондропластики, ассоциированной с применением PRP [25].…”
Section: костнохрящевые дефектыunclassified
“…The repair of cartilage defects poses some challenges due to the limited ability of tissue self‐healing and to the fact that current treatments often lead to the synthesis and deposition of fibrocartilage, which lacks the mechanical and functional properties of hyaline cartilage (Armiento, Alini, & Stoddart, ; Karuppal, ). The treatment of cartilage damages can be managed by administration of compounds such as corticosteroids (Jüni et al, ; Wernecke, Braun, & Dragoo, ), hyaluronic acid (Jang et al, ; Strauss, Schachter, Frenkel, & Rosen, ), and platelet‐rich plasma (Altan, Aydin, Erkocak, Senaran, & Ugras, ; Montañez‐Heredia et al, ).…”
Section: Introductionmentioning
confidence: 99%